Clinical outcome of Guillain-Barré syndrome after prolonged mechanical ventilation - van den Berg, Bianca; Storm, Eline F; Garssen, Marcel J P; Blomkwist-Markens, Patricia H; Jacobs, Bart C (Journal of neurology, neurosurgery and psychiatry, 2018)
BackgroundPatients with Guillain-Barré syndrome (GBS) may suffer from respiratory failure for months or longer. The aim of this study was to determine the frequency, clinical course and outcome of patients with GBS requiring prolonged mechanical ventilation (MV).MethodsProspectively collected data from 526 patients with GBS participating in previous trials were analysed to determine the frequency and duration of prolonged MV (longer than 2 months). In addition, a cross-sectional study was conducted in patients with GBS requiring MV to determine the clinical course and long-term outcome with the ability to walk unaided as primary endpoint.ResultsIn the cohort study, 145 of 526 patients with GBS (28%) required MV, including 33 (6%) patients with prolonged MV. Patients requiring prolonged MV had a lower Medical Research Council sum score and more frequent bulbar involvement and inexcitable nerves compared with shorter ventilated patients. At 6 months, 18% of patients with prolonged MV were able to walk unaided compared with 76% of patients requiring shorter MV (P<0.001). In the cross-sectional study, 63 patients requiring MV were included with a median follow-up of 11 years (range 2–44 years). Twenty-six (41%) of these patients needed prolonged MV (median 93 days, range 62–261). Fifteen (58%) of these patients were able to walk unaided at maximum follow-up and eight (31%) reached this endpoint more than 1 year after diagnosis.ConclusionsProlonged ventilation in GBS is associated with poor prognosis, yet patients requiring prolonged ventilation may show slow but persistent recovery for years and even reach the ability to walk and live independently.